2015
DOI: 10.1016/j.joa.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of primary and secondary prevention indications on anxiety about the implantable cardioverter‐defibrillator

Abstract: BackgroundImplantable cardioverter-defibrillators (ICDs) have been established for primary and secondary prevention of fatal arrhythmias. However, little is known about the influence of ICD indications on quality of life (QOL) and psychological disturbances. This study aimed to examine whether there were differences in QOL and psychological distress in patients that have an ICD for primary or secondary prevention of fatal arrhythmias.MethodsA multicenter survey of 179 consecutive outpatients (29.1% primary pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(41 reference statements)
1
15
1
Order By: Relevance
“…21 In contrast, more recently, Rahmawati et al showed that primary prevention was associated with general anxiety and poor QOL compared with secondary prevention. 16 This inconsistency may be attributed to the small sample sizes of patients and different assessments of psychological functioning that were employed F I G U R E 3 Alteration of the FSAS score over the 12-month follow-up period (female and male patients). FSAS = Florida Shock Anxiety Scale across studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 In contrast, more recently, Rahmawati et al showed that primary prevention was associated with general anxiety and poor QOL compared with secondary prevention. 16 This inconsistency may be attributed to the small sample sizes of patients and different assessments of psychological functioning that were employed F I G U R E 3 Alteration of the FSAS score over the 12-month follow-up period (female and male patients). FSAS = Florida Shock Anxiety Scale across studies.…”
Section: Discussionmentioning
confidence: 99%
“…ICD‐related anxiety may lead to increased device concerns, avoidance of behaviors, and limitations in performing everyday activities owing to possible future shock therapies . Previous studies indicated that ICD‐related anxiety is associated with reduced health‐related QOL, psychological distress, and even the risk of mortality . However, the current patient‐reported outcome studies that are available on ICD patients are composed predominantly of patients in the Western world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of appropriate therapy by ICD insertion has been reported to be higher in patients in whom the device was implanted for secondary prevention than in patients in whom the device was implanted for primary prevention . Clinical trials on ICD therapy have been mainly conducted in European countries and the United States, where most cases of underlying heart disease are ischemic heart disease, and thus, the findings may not be necessarily applicable to countries with different prevalences of heart diseases such as Japan, where SHD in 51%‐69% of candidates for ICD therapy is cardiomyopathy . In the Japanese guidelines of ICD implantation for secondary prevention, both documented ventricular fibrillation (VF) and hemodynamically unstable ventricular tachycardia (VT) in SHD are class I indication.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although appropriate ICD shocks improve survival, shocks may cause anxiety and psychological distress and increase mortality. [5][6][7][8] The PainFree SST clinical study was conducted to evaluate the efficacy of a novel suite of detection algorithms designated as "Smart Shock Technology." Use of this technology combined with modern programming led to a very low inappropriate shock rate in the range of 1.5% per year for dual-chamber ICDs.…”
Section: Introductionmentioning
confidence: 99%